The Function of DNA Polymerase α at Telomeric G Tails Is Important for Telomere Homeostasis - Martin, Aegina Adams (American Society for Microbiology, 2000)
Telomere length control is influenced by several factors, including telomerase, the components of telomeric chromatin structure, and the conventional replication machinery. Although known components of the replication machinery can influence telomere length equilibrium, little is known about why mutations in certain replication proteins cause dramatic telomere lengthening. To investigate the cause of telomere elongation in cdc17/pol1 (DNA polymerase α) mutants, we examined telomeric chromatin, as measured by its ability to repress transcription on telomere-proximal genes, and telomeric DNA end structures in pol1-17 mutants. pol1-17 mutants with elongated telomeres show a dramatic loss of the repression of telomere-proximal genes, or telomeric silencing. In addition, cdc17/pol1 mutants grown under telomere-elongating conditions exhibit significant increases in single-stranded character in telomeric DNA but not at internal sequences. The single strandedness is manifested as a terminal extension of the G-rich strand (G tails) that can occur independently of telomerase, suggesting that cdc17/pol1 mutants exhibit defects in telomeric lagging-strand synthesis. Interestingly, the loss of telomeric silencing and the increase in the sizes of the G tails at the telomeres temporally coincide and occur before any detectable telomere lengthening is observed. Moreover, the G tails observed in cdc17/pol1 mutants incubated at the semipermissive temperature appear only when the cells pass through S phase and are processed by the time cells reach G(1). These results suggest that lagging-strand synthesis is coordinated with telomerase-mediated telomere maintenance to ensure proper telomere length control.